Effect of Bupivacaine at Gallbladder Fossa and Port Site Vs Port Site Alone on Postop Analgesia in Lap Cholecystectomy - Hasham Ashraf, Muhammad; Naveed, Muhammad; Hassan, Maazul; Ahmad Khan, Rizwan; Khaliq Khan, Fareeha; Ara, Jahan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the effect of bupivacaine at gallbladder fossa and port site vs port site alone on postoperative pain in patients undergoing laparoscopic cholecystectomy. Methodology: After approval from ethical committee, 82 patients fulfilling the inclusion criteria were selected from department of General Surgery (West Surgical Ward), Mayo hospital Lahore. Demographic profile i.e. name, age, gender was recorded. All the patients were randomly divided into 2 groups. Results: The group statistics revealed that the visual analogue scale (VAS) was analyzed within the durations of 3, 6, 12 and 24 hours along with postoperative analgesia request. VAS at 3 hours showed that mean±SD of group 1 was 6.66±1.575 whereas group 2 showed relatively less values in mean±SD i.e. 4.0±1.162. VAS at 6 hours showed that mean±SD of group 1 was 6.2±1.04 whereas group 2 showed relatively less values in mean±SD i.e. 3.8±0.97. VAS at 12 hours showed that mean±SD of group 1 was 5.8±1.01 whereas group 2 showed relatively less values in mean±SD i.e. 3.7± 0.89. VAS at 24 hours showed that mean±SD of group 1 was 5.3±0.89 whereas group 2 showed less values in mean± SD i.e. 3.3±0.69. Post-operative analgesia duration in group 1 was also recorded, the mean±SD hours of group 1 was 3.49±1.26, whereas for group 2, the mean±SD hours were 6.4±1.70. Independent sample t test is applied between VAS pain score at 3, 6, 12 and 24 hours between the group 1 and 2, and 1st request for the post-operative analgesia is recorded. The p value is <0.05 which is significant statistically. Conclusion: Adequate post-operative pain control provides early post-surgical mobilization, shortened hospital stay and increased patient satisfaction. This also reduces requirement of postoperative opioid analgesics.